2002
DOI: 10.1046/j.1365-294x.2002.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern of chloroplast DNA variation of Cyclobalanopsis glauca in Taiwan and East Asia

Abstract: This study examined the spatial pattern of chloroplast DNA (cpDNA) variation in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. (Fagaceae) in 140 trees from Taiwan (25 populations), Japan (three), Ryukyus (two), Hong Kong (one) and Mainland China (one). By sequencing three cpDNA intergenic spacer fragments using universal primers (trnT-trnL, trnV-trnM, including the trnV intron, and petG-trnP), we found a total of 1,980 bp and 15 polymorphic sites. Among them, 12 sites were caused by point mutation, and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 31 publications
(25 reference statements)
7
84
0
Order By: Relevance
“…A similar effect was also observed in a study of Cy. glauca (Huang et al 2002) and such animal species as the rice frog, Rana limnocharis (Toda et al 1998), and tree squirrel, Callosciurus erythraeus (Lee 2003). Differences in values of N ST -G ST among populations were not significant in any situation revealing that no phylogeographical structure exists among the haplotypes (Table 3).…”
Section: Range Expansion After the Glacial Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect was also observed in a study of Cy. glauca (Huang et al 2002) and such animal species as the rice frog, Rana limnocharis (Toda et al 1998), and tree squirrel, Callosciurus erythraeus (Lee 2003). Differences in values of N ST -G ST among populations were not significant in any situation revealing that no phylogeographical structure exists among the haplotypes (Table 3).…”
Section: Range Expansion After the Glacial Periodmentioning
confidence: 99%
“…Using cpDNA polymorphism and nucleotide diversity, Huang et al (2002) proposed that the southeastern part of Taiwan might have been a potential refugium for Cyclobalanopsis (or Quercus) glauca, a widespread subtropical species. Using a similar strategy, Huang et al (2004) inferred that the north-central region, west of the central mountain range (CMR) was a potential refugium for Trochodendron aralioides, a temperate species, during the last glaciation.…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses show that genetic diversity in M. decussata is partitioned among the population sites. High differentiation of populations in M. decussata is similar to those of some long-lived, wind-pollinated species with fragmented distributions (Huang et al 2002;Petit et al 2005;Jaramillo-Correa et al 2006;Provan et al 2007). The significantly higher value for N ST than G ST indicates that closely related haplotypes are more likely to co-exist in the same populations (Pons and Petit 1996;Petit et al 2005).…”
Section: Discussionmentioning
confidence: 55%
“…Stars indicate the clades in which geographic associations are significant with the nested contingency analysis (P \ 0.05) and for which the chains of inference are shown: 1-2 IO-inconclusive outcome; 1-2-3-4 NOrestricted gene flow with isolation by distance; 1-2-11-12 NOcontiguous range expansion we found that there is the considerable level of haplotype diversity along with the low level of nucleotide diversity in M. decussata (Table 4). The level of cpDNA variation in M. decussata is congruous to that in some other woody species, such as Pinus sylvestris (h, 0.950-0.987;Provan et al 1998), Cyclobalanopsis glauca (p, 0.00065;h, 0.68;Huang et al 2002), Cunninghamia konishii and C. lanceolata (p, 0.00190 and p, 0.00176, respectively; Hwang et al 2003), and Pinus nigra (h, 0.939-1.00; AfzalRafii and Dodd 2007). A large number of haplotypes with low nucleotide diversity found in M. decussata may be a consequence of homoplasy or may result from rapid population growth of an ancestral population with a low effective population size (Abramson 2007).…”
Section: Discussionmentioning
confidence: 83%
“…The previously published pri mer pairs (Table 1) and recommended PCR parameters (Les ki nen & AlströmRapaport 1999, Mir et al 2010, Ham zaBabiker et al 2009, Huang et al 2002, Shaw et al 2005 were used to amplify these regions. Amplification and sequencing reactions were carried out in a GeneAmp PCR System 9700 thermal cycler (Applied Biosystems, USA).…”
Section: Dna Isolation Amplification and Sequencingmentioning
confidence: 99%